Ravana tries to lift Mt Kailasa where Shiva and Parvathi reside - 111 - Brig Ajai Singh (2022)
Image courtesy: Brig A.P. Singh - www.collectingmoment.in Story from chapter 16 of the Uttara-kanda of the epic Ramayana. The chapter is titled 'The Origin of Ravana’s Name'